Relationships of Mental Health With Psychological Vulnerability in Nurses Working in COVID-19 Wards: Mediated by Emotional Processing and Perceived Social Support - Rozita Mazhari; Abdolhassan Farhangi; Farah Naderi (Gonabad University of Medical Sciences, 2022)
Background: Working in a hospital involves a lot of long-term stress, which affects people who work in helping professions and are immersed in others' problems. The present study aimed to determine the relationships between psychological capital, mental health, and health anxiety with psychological vulnerability through the mediating role of emotional processing and perceived social support in nurses working in COVID-19 wards in Shiraz City, Iran, in 2021. Methods: This research is a correlational study using structural equation modeling (SEM). The sample size included 200 nurses from the COVID-19 unit of hospitals in Shiraz. The samples were selected through multistage random sampling. Accordingly, five hospitals in Shiraz were selected randomly, and then, 200 nurses were selected from their COVID-19 unit. The research instruments included the psychological vulnerability scale, the general health questionnaire-28, the psychological capital questionnaire, the health anxiety questionnaire, the emotional processing scale, and the multidimensional scale of perceived social support. The data were analyzed in AMOS-25 using SEM and Pearson correlation coefficient. Results: The SEM showed that the proposed model fitted the data well. The direct paths from perceived social support, psychological capital, emotional processing, and mental health to psychological vulnerability were negative and significant (P<0.01). The relationships of health anxiety with psychological vulnerability and perceived social support, emotional processing with mental health, and psychological capital with perceived social support were all positive and significant (P<0.01). There was no significant direct relationship between health anxiety and perceived social support and between psychological capital and emotional processing. Conclusion: Psychological capital and emotional processing played effective roles in reducing nurses' psychological vulnerability and could thus be used to mitigate psychological damages caused by working during the COVID-19 pandemic.